Rancang Bangun Website Tour Guide Pintar Berbasis Lokasi dengan Rekomendasi Tempat Otomatis di Batam. - Hadi Susanto; Eka Lia Febrianti (Fakultas Komputer - Universitas Universal, 2026)
Tourism in Batam City is growing rapidly, yet independent travelers still face difficulties in obtaining accurate, affordable, and efficient destination information. This study aims to design and develop a location based smart tour guide website equipped with an automatic travel recommendation feature using the Content Based Filtering algorithm and geographic zone clustering based on subdistricts in Batam. The system was developed using the Waterfall method with PHP native and MySQL technology, integrated with the Google API for precise location mapping. The system generates daily itinerary recommendations automatically based on tourism category preferences entered by the user, taking into account geographic efficiency between sub-districts. Testing results involving 52 respondents showed that 59,6% were very satisfied and 30,8% satisfied with the overall appearance of the website.